2014
DOI: 10.3389/fcell.2014.00072
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial metabolism and the control of vascular smooth muscle cell proliferation

Abstract: Differentiation and dedifferentiation of vascular smooth muscle cells (VSMCs) are essential processes of vascular development. VSMC have biosynthetic, proliferative, and contractile roles in the vessel wall. Alterations in the differentiated state of the VSMC play a critical role in the pathogenesis of a variety of cardiovascular diseases, including atherosclerosis, hypertension, and vascular stenosis. This review provides an overview of the current state of knowledge of molecular mechanisms involved in the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
82
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(89 citation statements)
references
References 99 publications
4
82
0
1
Order By: Relevance
“…Studies have demonstrated that abnormal proliferation of vascular smooth muscle cells (VSMCs) play a critical role in the pathogenesis of cardiovascular diseases 456. However, to our best knowledge, the underlying molecular mechanisms thereof remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have demonstrated that abnormal proliferation of vascular smooth muscle cells (VSMCs) play a critical role in the pathogenesis of cardiovascular diseases 456. However, to our best knowledge, the underlying molecular mechanisms thereof remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…by phenotype change switch over to its synthetic/ proliferative type and fibroblasts switch to 286 myofibroblasts which has features similar to VSMC (synthetic /proliferative ) phenotype but are 287 hyper contractile. In spirit of aerobic glycolysis / proliferation happening in these states i will call 288 these states as Warburg irreversible dedifferentiation states (68,77). But what triggers this cell phenotype change apart from the glycolysis shift?…”
Section: Warburg Common Pathogenesis Model In Sepsis (Figure 2): 173mentioning
confidence: 99%
“…VSMC proliferation / dedifferentiation have been 263 already related to various pathologies and this change has been related to Warburg effect (68). 264…”
Section: Warburg Common Pathogenesis Model In Sepsis (Figure 2): 173mentioning
confidence: 99%
“…However, in response to vascular damage or inflammatory stimulations, VSMCs may undergo phenotypic changes to an uncontrolled proliferating and migratory state (1). It has been well established that the abnormal proliferation and migration of VSMCs in arterial walls is crucial in the development and progression of cardiovascular disorders, including intimal hyperplasia, arteriosclerosis and restenosis following percutaneous coronary intervention (PCI) (2,3).…”
Section: Introductionmentioning
confidence: 99%